Fostering Inclusive Arabic Language Education through a Humanistic Approach Mewujudkan Pendidikan Bahasa Arab yang Inklusif melalui Pendekatan Humanistik - Hanna Nor Fadhilah; Ika Oktaviani; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article explores the application of humanistic approaches in Arabic language learning, emphasizing the holistic development of students, which includes cognitive, emotional, and social aspects. Humanistic theories, such as Maslow’s Hierarchy of Needs, Carl Rogers’ Student-Centered Learning, intrinsic motivation, emotional intelligence, and Islamic humanism, serve as the foundation for a learning process that prioritizes students' individual needs over mere academic achievement. The role of the teacher as a facilitator is highlighted, where the teacher not only imparts knowledge but also creates a supportive environment to encourage student engagement, critical thinking, and emotional growth. Furthermore, the article examines the challenges of implementing humanistic approaches, such as diverse student needs, time constraints, limited resources, and lack of understanding of the approach itself, while offering potential solutions to address these obstacles. Ultimately, the article concludes that the humanistic approach in Arabic language education creates a meaningful, dynamic, and supportive learning environment that fosters the overall growth of students, not only academically but also socially and emotionally.